How Vertical and Horizontal Pay Gaps in Research and Development Affect Corporate Innovation in Indonesian Public Firms - Budiandriani; Fahlevi Mochammad (ECONOMICS)
This study examines how vertical and horizontal pay disparities influence corporate innovation in publicly listed Indonesian firms from 2018 to 2022. Using a dataset of 1,505 firm-year observations, we apply Social Comparison Theory to analyze how perceived compensation inequalities impact innovation performance, measured by patent filings and citations. To ensure robustness, we employ Ordinary Least Squares (OLS), Two-Stage Least Squares (2SLS), Propensity Score Matching (PSM), Difference-in-Differences (DID), Entropy Balancing, and Tobit Regression. The results indicate that vertical pay disparity (CV_MT-RDP) positively affects patent quantity but negatively impacts patent quality, implying that larger managerial pay gaps encourage more patents but may not enhance their impact. Conversely, horizontal pay disparity (CV_RDP-OE) consistently reduces both patent output and citation impact, demonstrating that excessive pay differences across departments undermine cross-functional collaboration and innovation efficiency. Further, state-owned enterprises (SOEs) experience stronger negative effects of pay disparities on innovation than private firms, reinforcing the role of fairness concerns in shaping employee motivation. These findings suggest that firms should strategically design compensation policies to balance tournament incentives and pay equity to sustain long-term innovation performance.